Dāniw Ancestors, Ritual, and Officiant as a Form of Authority in Mangyan Patag Society (Southeast Mindoro) - Luquin, Elizabeth (2021)
The Mangyan Patag in southeastern Mindoro encapsulate the relational nature of beings, such as humans, in the concept of ‘āpu, a polysemic term that designates ancestors in general. One type of ‘āpu is the dāniw, who, forming a pair (even number) in a relationship with humans, enables ritual officiants to enter the invisible world of spirits, restore a destructive situation, and maintain the continuity of society. When in a relationship with humans by odd numbers, ancestors called hiri’ enable officiants to kill for personal purposes. However, the personal power of hiri’ ancestors is subordinate to the authority of dāniw ancestors.
Keywords: Ancestor worship; Social life and customs of indigenous peoples; Mangyan (Philippine people)